Tác động của mức độ quan tâm của nhà đầu tư tới rủi ro sụt giảm giá cổ phiếu trên thị trường chứng khoán Việt Nam - Lê Hải, Trung (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
The study evaluates the impacts of investor attention, proxied by the search volume for each individual stock ticker from Google Trends Analytics, on the crash risk of the stock price of listed firms on the Vietnamese stock market. Specifically, this research investigates the impact of the frequency of searching for information about the stocks of investors on the Google platform on the price crash risk by using data from 206 firms listed on the Vietnamese stock market from 2013 to 2022. Our empirical analysis reveals that investor attention on individual securities is positively correlated with stock price crash risk. The author further explores the heterogenous impacts of firm size, and liquidity, and finds that the positive impacts of investor attention are stronger for bigger and higher liquidity stock. This finding is consistent with the fact that the Vietnamese stock market is dominated by retail investors. Thus, the investor tends to overreact and have herding behaviors, which eventually results in higher crash risks during the stock correction phase.
Keywords: Investor attention; Crash risk; Stock market